Magnon Polarons Induced by a Magnetic Field Gradient - Vidal-Silva, N (American Physical Society, 2020)
In this paper, we report the theoretical possibility of generating magnon-polaron excitations through a space-varying magnetic field. The spatial dependence of the magnetic field in the Zeeman interaction gives rise to a magnon-phonon coupling when a magnetic field gradient is applied, and such a coupling depends directly on the strength of the gradient. It is also predicted that the direction of the magnetic field gradient allows control over which phonon polarization couples to the magnons in the material. Here, we develop the calculations of the magnon-phonon coupling for an arbitrary (anti)ferromagnet, which are later used to numerically study its consequences. These results are compared to the ones obtained with the phenomenological magnetoelastic coupling in yttrium iron garnet (YIG) where we show that the magnon-polaron band gap seen in YIG can be also obtained with a magnetic field gradient of ∼0.1T/m which can be achieved with the current experimental techniques. Our results propose a different way of controlling the magnetoelastic coupling in an arbitrary material and open a route to exploit the magnon-phonon interaction in magnonic and spintronic devices. © 2020 American Physical Society.